SHIP‐1, a target of miR‐155, regulates endothelial cell responses in lung fibrosis. Issue 2 (12th December 2019) - Tang, Haiying; Mao, Jingwei; Ye, Xujun; Zhang, Fengrui; Kerr, William G.; Zheng, Tao; Zhu, Zhou
Abstract: Src Homology 2‐containing Inositol Phosphatase‐1 (SHIP‐1) is a target of miR‐155, a pro‐inflammatory factor. Deletion of the SHIP‐1 gene in mice caused spontaneous lung inflammation and fibrosis. However, the role and function of endothelial miR‐155 and SHIP‐1 in lung fibrosis remain unknown. Using whole‐body miR‐155 knockout mice and endothelial cell–specific conditional miR‐155 (VEC‐Cre‐miR‐155 or VEC‐miR‐155) or SHIP‐1 (VEC‐SHIP‐1) knockout mice, we assessed endothelial‐mesenchymal transition (EndoMT) and fibrotic responses in bleomycin (BLM) induced lung fibrosis models. Primary mouse lung endothelial cells (MLEC) and human umbilical vein endothelial cells (HUVEC) with SHIP‐1 knockdown were analyzed in TGF‐β1 or BLM, respectively, induced fibrotic responses. Fibrosis and EndoMT were significantly reduced in miR‐155KO mice and changes in EndoMT markers in MLEC after TGF‐β1 stimulation confirmed the in vivo findings. Furthermore, lung fibrosis and EndoMT responses were reduced in VEC‐miR‐155 mice but significantly enhanced in VEC‐SHIP‐1 mice after BLM challenge. SHIP‐1 knockdown in HUVEC cells resulted in enhanced EndoMT induced by BLM. Meanwhile, these changes involved the PI3K/AKT, JAK/STAT3, and SMAD/STAT signaling pathways. These studies demonstrate that endothelial miR‐155 plays an important role in fibrotic responses in the lung through EndoMT. Endothelial SHIP‐1 is essential in controlling fibrotic responses and SHIP‐1 is a target of miR‐155. Endothelial cells are an integral part in lung fibrosis.